Naramsîn und Ištar sitzen sich gegenüber Darstellung auf einer Steinform unklarer Nutzung - Braun-Holzinger, Eva Andrea (2017)
A fragment of a stone “mould” shows the deified Naramsîn and Ištar, both sitting on a stepped construction. This extraordinary image is set in a mythic scenery with mountain-gods and a water-goddess. Philologists and archaeologists alike were inspired by this intricate image; their interpretations are manifold and erudite, nevertheless highly speculative. But, alas, this unique objet d’art is without known provenance. All the motifs of this tableau are known from other Near Eastern artefacts, but all of them show aberrations that are at fault with the well-known Mesopotamian iconographic conventions of the 3rd millennium BC. The technique of the engraving excludes the use of this stone as a mould; moreover, the arrangement of the scenes in radial segments runs contrary to Near Eastern norms for decorating circular objects.1